2015
DOI: 10.3892/or.2015.4510
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of tumor expression of major histocompatibility complex class I-related chains A and B (MICA/B) in gastric cancer patients

Abstract: Gastric cancer (GC) is the third most common cause of cancer death worldwide. Natural killer cells play an important role in the immune defense against transformed cells. They express the activating receptor NKG2D, whose ligands belong to the MIC and ULBP/RAET family. Although it is well established that these ligands are generally expressed in tumors, the association between their expression in the tumor and gastric mucosa and clinical parameters and prognosis of GC remains to be addressed. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
0
14
2
2
Order By: Relevance
“…The expression of MHC class I in carcinoma cells may induce cytotoxic effects of lymphocytes and other immune cells (27,28). Carcinoma cells that do not express MHC class I may evade from the cytotoxic effects of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MHC class I in carcinoma cells may induce cytotoxic effects of lymphocytes and other immune cells (27,28). Carcinoma cells that do not express MHC class I may evade from the cytotoxic effects of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these two pathways were significantly enriched with major histocompatibility complex (MHC), class II, DRβ5 (HLA-DRB5), MHC class II, DMα (HLA-DMA), MHC class II, DQα1 (HLA-DQA1), and MHC class II, DRα (HLA-DRA), which encode important MHC class II molecules on antigen-presenting cells. Ribeiro et al found that the expression of MHC class I-related chains A and B in tumors may be involved in the progression of GC and be of predictive value for prognosis in GC with large tumors ( 32 ). This suggested that HLA-DRB5, HLA-DMA, HLA-DQA1 and HLA-DRA may be of predictive value for survival rates of patients with GC.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MICA and MICB proteins has been reported for many tumour types, with high expression associated with poor prognosis ( Spear et al , 2013 ). In contrast expression of MICA and MICB has been reported to be restricted to only a few normal tissue types, including gastrointestinal tract epithelium ( Groh et al , 1996 ; Allegretti et al , 2013 ), and adjacent normal mucosa from gastric cancer patients ( Ribeiro et al , 2015 ). MICA/B is also reported to be shed from the surface of cancer cells ( Salih et al , 2008 ; Zhang et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%